Multi-path backup optimized power algorithm for wideband networks - XU Yu-bin; TAN Wei (Tongxin xuebao)
A multi-path backup optimized power algorithm was presented for wideband network, which exerted multi-path backup routing and reduced the total transmission power. This algorithm was suitable for structure-changed mobile ad hoc network and power-restricted UWB network. The simulation result shows that the new algorithm can increase the throughput of network and improve delay and overhead.